Dysregulated Lipid Transport Proteins Correlate With Pathogenesis and Outcome in Severe Alcoholic Hepatitis - Maras, Jaswinder Singh (Hepatol Commun, 2019)
Severe alcoholic hepatitis (SAH) has high mortality. Dysregulated lipid transport and metabolism in liver/macrophages contributes to disease pathophysiology. Paraoxonase/arylesterase 1 (PON1), a liver‐specific enzyme, inhibits oxidation of phospholipids and prevents lipid‐mediated oxidative damage. However, its functional contribution in macrophage‐mediated hepatic injury warrants elucidation. Plasma proteome of patients with SAH (n = 20), alcoholic cirrhosis (n = 20), and healthy controls was analyzed. Dysregulated pathways were identified, validated, and correlated with severity and outcomes in 200 patients with SAH. Tohoku‐Hospital‐Pediatrics‐1 (THP1)‐derived macrophages were treated with plasma from study groups in the presence/absence of recombinant PON1 and the phenotype; intracellular lipid bodies and linked functions were evaluated. In patients with SAH, 208 proteins were >1.5 fold differentially regulated (32 up‐regulated and 176 down‐regulated; P < 0.01).Validation studies confirmed lower levels of lipid transporter proteins (Pon1, apolipoprotein [Apo]B, ApoA1, ApoA2, and ApoC3; P < 0.01). Low PON1 levels inversely correlated with severity and mortality (r(2) > 0.3; hazard ratio, 0.91; P < 0.01) and predicted nonsurvivors (area under the receiver operating characteristic curve, 0.86; cut‐off, <18 μg/mL; log rank, <0.01). Low PON1 levels corroborated with increased oxidized low‐density lipoprotein levels, intracellular lipid bodies, lipid uptake, lipid metabolism, biosynthesis, and alternative macrophage activation genes in nonsurvivors (P < 0.01). Importantly, in vitro recombinant PON1 treatment on THP1 macrophages reversed these changes (P < 0.01), specifically by alteration in expression of clusters of differentiation 36 (CD36) and adenosine triphosphate‐binding cassette subfamily A1 (ABCA1) receptor on macrophages. Conclusion: Lipid transport proteins contribute to the pathogenesis of SAH, and low PON1 levels inversely correlate with the severity of alcoholic hepatitis and 28‐day mortality. Restitution of circulating PON1 may be beneficial and needs therapeutic evaluation in patients with SAH.